Effect of azithromycin on a red complex polymicrobial biofilm. Issue 1 (1st January 2017) - Ong, Hwei Sze; Oettinger-Barak, Orit; Dashper, Stuart G.; Darby, Ivan B.; Tan, Kheng H.; Reynolds, Eric C.
ABSTRACT: Azithromycin has recently gained popularity for the treatment of periodontal disease, despite sparse literature supporting efficiency in treating periodontal bacterial biofilms. The aim of this study was to evaluate the effect of azithromycin on biofilms comprised of Porphyromonas gingivalis, Treponema denticola, and Tannerella forsythia in comparison to an amoxicillin and metronidazole combination. P. gingivalis W50, T. denticola ATCC35405, and T. forsythia ATCC43037 grown under anaerobic conditions at 37°C were aliquoted into 96-well flat-bottom plates in different combinations with addition of azithromycin or amoxicillin + metronidazole at various concentrations. For the biofilm assay, the plates were incubated at 37°C anaerobically for 48 h, after which the biofilms were stained with crystal violet and measured for absorbance at AU620 . In this model, polymicrobial biofilms of P. gingivalis  +  T. denticola, P. gingivalis  +  T. forsythia, and T. denticola  +  T. forsythia were cultured. Combination of all three bacteria enhanced biofilm biomass. Azithromycin demonstrated a minimal biofilm inhibitory concentration (MBIC) of 10.6 mg/L, while the amoxicillin + metronidazole combination was more effective in inhibiting biofilm formation with a MBIC of 1.63 mg/L. Polymicrobial biofilm formation was demonstrated by combination of all three red complex bacteria. Azithromycin was ineffective in preventing biofilm formation within a clinically achievable concentration, whereas the combination of amoxicillin and metronidazole was more effective for this purpose.